Criminal Liability of A Notary as A Helper Criminal Acts of Corruption - Amadya, Maritsa Adnina Luvy (Eduvest - Journal of Universal Studies, 2025)
This paper examines the legal accountability of notaries involved in corruption crimes, focusing on the case of Decision 51/Pid.Sus-TPK/2022/PN PBR, where a notary with the initials DF was found guilty of assisting in the process of granting credit that violated the law, resulting in financial losses for banks. This study formulates problems related to the duties and responsibilities of notaries in making cover notes and criminal liability arising from their involvement in corruption crimes. The results of the study show that although the cover note is not explicitly regulated in the law, its existence is important in the credit disbursement process, and notaries can be held liable both criminally and civilly if they are involved in illegal acts. The conclusions of this study confirm that notaries must carry out their duties with integrity to avoid serious legal consequences.